Enhanced Face Recognition Method Performance on Android vs Windows Platform - Alsibai, Mohammad Hayyan; Hadi, Manap; Abdul Adam, Abdullah (Asian Research Publishing Network (ARPN), 2015)
Android is becoming one of the most popular operating systems on smartphones, tablet computers and similar mobile devices. With the quick development in mobile device specifications, it is worthy to think about mobile devices as current or - at least - near future replacement of personal computers. This paper presents an enhanced face recognition method. The method is tested on two different platforms using Windows and Android operating systems. This is done to evaluate the method and to compare the platforms. The platforms are compared according to two factors: development simplicity and performance. The target is evaluating the possibility of replacing personal computers using Windows operating system by mobile devices using Android operating system. Face recognition has been chosen because of the relatively high computing cost of image processing and pattern recognition applications comparing with other applications. The experiment results show acceptable performance of the method on Android platform.